Treatment of relapse Ameloblastoma after Hemimandibulectomy and Mandibular Reconstruction - Putri, Dian Maifara; Hardianto, Andri; Syamsudin, Endang; Rizki, Kiki Akhmad (Padjadjaran Journal of Dentistry, 2015)
Background. Ameloblastoma is a benign odontogenic tumor with an aggressive biological behaviour, and the surgical treatment frequently results in failure for the post operative recurrence. Purpose. The aim of this study was to evaluate the clinical result of the patient with aggressive recurrent ameloblastoma who underwent two times radical surgery to get recurrence free. Case. We report a patient who was diagnosed with ameloblastoma of the mandible 13 years ago and had undertaken operation hemimandibulectomy and mandibular reconstruction. However, recurrence occured and secondary surgical treatment (particularly radical) offers the best chance to the patient. The recurrence of an ameloblastoma mainly displays the ineffectiveness or perhaps lack of success of the main surgical treatment. Conclusion. The method has to be intense as well as radical in order to steer clear of reccurence. For ameloblastoma an ineffectiveness of initial surgical treatment indicates that more radical strategy led to minimum recurrence rate.